Niède Guidon, Serra da Capivara and celestial records in rock art: science, culture and archaeoastronomy in the Piauí caatinga - Corte, Viviana Borges; Rabelo, Rizalva dos Santos Cardoso (Cadernos de Astronomia, 2025)
This article explores the trajectory of archaeologist Niède Guidon and her scientific-cultural legacy based on her discoveries in Serra da Capivara, Piauí. Based on her contribution to Brazilian archaeology and the importance of Serra da Capivara National Park as a world heritage site, we discuss the role of science and education in preserving historical memory and valuing indigenous cultures. Finally, we analyze the archaeoastronomical potential of the region's rock paintings, exploring the possible relationship between prehistoric graphic records and celestial observations of its ancient inhabitants. The analysis adopts an interdisciplinary perspective, integrating archaeology, cultural astronomy and history of science.
Keywords: Niède Guidon; Serra da Capivara; rock art; archaeoastronomy; science popularization